Principles of Evolutionary Medicine - Gluckman, Peter et.al (Oxford Oxford University Press, 2016)
A new updated edition of the first integrated and comprehensive textbook to explain the principles of evolutionary biology from a medical perspective and to focus on how medicine and public health might utilise evolutionary biology.
Include Colour Illustrations, References and Index
Keywords: Human evolution -- Medical anthropology -- Medical genetics